A study on carbon formation over fibrous NiO/CeO2 nanocatalysts during dry reforming of methane - Wang, Zhitao; Shao, Xin; Larcher, A.; Xie, K.; Dong, Dehua; Li, Chun-Zhu (Elsevier BV, 2013)
Dry reforming of methane over novel fibrous NiO/CeO2 nanocatalysts was studied to investigate the influence of catalyst microstructure and gas flow rate on carbon formation. X-ray diffraction confirmed no solid solution formed during the template synthesis of the NiO/CeO2 nanocatalysts by eggshell membranes. Catalyst microstructure changed with NiO content and crystallization temperature according to scan electron microscopy images. Temperature-programmed reduction profiles revealed the catalyst microstructure greatly affected the interaction between NiO and CeO2 support, which determined carbon formation because CeO2 support provided oxygen species to oxidize carbonaceous deposits on catalyst surface. The stronger interaction resulted in the lower coke formation rate and the higher methane conversion. Carbon formation rate was also studied as a function of the rate of gas flow passing through the fibrous catalysts. Increasing the gas flow rate could substantially reduce carbon formation rate, and it might be attributed to the facilitated radical desorption and/or low methane conversions at high gas flow rates.